Evaluación de películas poliméricas basadas en almidón de maíz, ácido poliláctico y polivinil alcohol como alternativa para la sustitución de polímeros convencionales a nivel laboratorio (2020)
This grade project seeks to evaluate the properties of biopolymers from polymer mixtures of corn starch, polylactic acid and polyvinyl alcohol that can replace conventional polymers used in the development of a medical product (external dressing layer) for the nanotechnology and biotechnology research center of Tecnoparque as it wants to produce a 100% biodegradable product. To achieve this purpose, a series of tests were carried out in order to establish the necessary parameters for obtaining the mixtures and polymer films that were subsequently subjected to a wet heat sterilization process to determine whether the temperature and time at which this process is performed could produce any thermal degradation effect on polymer films, at this test could be determined that only two mixtures (90% PVOH and 100% PVOH with respect to starch) met this characteristics. Finally these two mixtures were subjected to the permeability test to water vapour, thus favoring the mixture containing 100% PVOH with respect to starch, which was characterized by measuring its permeability to water, density, water adsorption, degradation resistance and biodegradability.